TEKNOLOGI PEMBUATAN PAVING BLOCK DENGAN MATERIAL FCA (FINE COARSE AGGREGATE) - Erwin Rommel (Jurnal Gamma, 2009)
Paving block most use in construction such as pavement, highway and parking area. Ease onsetting, cheap of treatment and aesthetic fully cause of paving block such as like. Production ofpaving block is not optimally from quality, because paving block still from the home industryproduct. The research is given production paving block with FCA (fine coarse aggregate) materialalternative another sand and cement. The strength paving block testing at some paving productwith full-pressing method, partial-pressing method and vibrating method.The research was done in UMM Laboratory and Home Industry. The six series paving blockconsist of cement : sand : FCA are 1:4:0, 1:4:3, 1:4:5, 1:8:0, 1:8:3, 1:8:5 respectively. Each variantwas made with pressing method (40, 60, 80 and 100 kg/cm2 respectively) and vibrating method,such as fully and partially method with totally specimen are 540 (each series was made 3 specimen).Curing method is done with spray water surface on paving block of age ; 7, 14, and 21 days,respectively.FCA paving block with full-pressing method can reach paving quality grade II, strength 276kg/cm2 at ratio 1:4:3, for partial-pressing maximum strength happened at ratio 1:4:0 (paving nonFCA) with strength 283 kg/cm2. The pressing method is better to compare with vibrating method,compression strength more than 200 kg/cm2, for partial-vibrating method (maximum strength is199 kg/cm2 at ratio 1:4:5, 21 day) strength result is better to compare with full-vibrating (strengthis 163 kg/cm2 at ratio 1:8:0, 21 day)